Impacts of a Multi-University REU Program. Issue 1762 (9th February 2015) - Barry, Carol; Isaacs, Jacqueline; Miller, Glen; Alpert, Carol Lynn
ABSTRACT: For nine years, an REU program placed over 200 undergraduate researchers at Northeastern University, the University of Massachusetts Lowell, and the University of New Hampshire through the NSF-funded Nanoscale Science and Engineering Center for High-rate Nanomanufacturing. The cross-university professional development program included university-based research skills, communication skills with the Boston Museum of Science, and a unique method for researcher evaluation of the societal impact of their decisions. This work presents the impacts of this research program as measured at program end, along with the career progress of the REU participants, recent interviews with REU participants, and reflections by REU program leaders.